1998
DOI: 10.1055/s-2006-957447
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities of Limonin Isolated from the Fruits ofEvodia rutaecarpavar.bodinieri

Abstract: Antinociceptive and anti-inflammatory effects of limonin isolated from the dried fruits of Evodia rutaecarpa var. bodinieri were investigated. Oral administration of 30 or 100 mg/kg limonin significantly decreased the frequency of licking and biting behavior within a unit of time at the late phase without affecting that of the early phase in the formalin test. Limonin inhibited the rise of vascular permeability induced by acetic acid and the increase of paw edema induced by carrageenin. Limonin also showed inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 4 publications
2
33
0
Order By: Relevance
“…Among them, the nitrogenous heterocyclic 4-(3H)-quinazolinones and substituted quinazolines represent a very important class of drugs with several biological properties, such as anticancer [11], diuretic [12], anti-inflammatory [13], anti-convulsant [14] and anti-hypertensive [15] activities.…”
Section: Quinazolinesmentioning
confidence: 99%
“…Among them, the nitrogenous heterocyclic 4-(3H)-quinazolinones and substituted quinazolines represent a very important class of drugs with several biological properties, such as anticancer [11], diuretic [12], anti-inflammatory [13], anti-convulsant [14] and anti-hypertensive [15] activities.…”
Section: Quinazolinesmentioning
confidence: 99%
“…A linear probe was placed in a 50 mL beaker containing STD 3 temperature. The probe was perfused with 10% (w/w) ethanol solution under a flow rate of 0.2 mL/hour (3.33 µL/minute).…”
Section: Ex Vivo Recovery Validationmentioning
confidence: 99%
“…2 With respect to the pharmacological actions of Evo and Rut, more attention has been paid to their antinociceptive activity and antiinflammatory effects. [3][4][5][6] In the authors' previous studies, topical administration of Evo and Rut at a ratio of 1:1 (w/w) elicited good antiinflammatory and analgesic effects in mice. Thus, Evo and Rut have the potential to be developed into topical antiphlogistic and analgesic preparations.…”
Section: Introductionmentioning
confidence: 99%
“…S1; supplementary material is available online at www .liebertpub.com/omi) is the major pharmacologically active protoberberine alkaloid in Phellodendri amurensis cortex and Coptidis rhizoma. Several studies have shown that berberine has antibacterial, antiviral, anti-nociceptive, anti-inflammatory, anti-carcinogenic in aflatoxin B1-induced hepatocellular carcinoma and inhibit p-glycoprotein (Mahmoud et al, 2014;Matsuda et al, 1998;Tundis et al, 2014). In vivo tests have shown that berberine inhibits carcinogen-induced tumor growth in various organs (Gong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%